2011
DOI: 10.1371/journal.pone.0016454
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin Is an Antibacterial, Stress-Inducible Peptide of the Biliary System

Abstract: Background/AimsHepcidin (gene name HAMP), an IL-6-inducible acute phase peptide with antimicrobial properties, is the key negative regulator of iron metabolism. Liver is the primary source of HAMP synthesis, but it is also produced by other tissues such as kidney or heart and is found in body fluids such as urine or cerebrospinal fluid. While the role of hepcidin in biliary system is unknown, a recent study demonstrated that conditional gp130-knockout mice display diminished hepcidin levels and increased rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Our data indicate that hepcidin expression in the stomach is IL-6-inducible, which is well in line with previous findings demonstrating that IL-6/STAT3 pathway is responsible for hepcidin upregulation in multiple tissues such as the liver, heart, biliary system as well as β-cells of pancreas and monocytes 3 9 12 34–36. IL-6/STAT3 pathway is also likely involved in the observed induction of gastric hepcidin in H pylori -infected cells/patients given that these conditions are associated with increased IL-6 levels 37–39.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data indicate that hepcidin expression in the stomach is IL-6-inducible, which is well in line with previous findings demonstrating that IL-6/STAT3 pathway is responsible for hepcidin upregulation in multiple tissues such as the liver, heart, biliary system as well as β-cells of pancreas and monocytes 3 9 12 34–36. IL-6/STAT3 pathway is also likely involved in the observed induction of gastric hepcidin in H pylori -infected cells/patients given that these conditions are associated with increased IL-6 levels 37–39.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, hepcidin was detected in human gastric juice (data not shown), which opens up the possibility that it might be released into the gastric lumen rather than the bloodstream. Although an exocrine secretion of hepcidin remains to be convincingly demonstrated, the presence of hepcidin in multiple body fluids such as saliva, pleura and ascites fluid as well as bile is consistent with this hypothesis 12 42. Another support for a luminal function of hepcidin in the gut came from a recent paper, which identified DMT1, a protein found at the apical membrane of enterocytes, as a novel hepcidin target 43.…”
Section: Discussionmentioning
confidence: 72%
“…Although previous reports have indicated a relationship between iron homeostasis and the auditory systems, the exact function in this process remains to be clarified (Cetin et al, 2004;Strnad et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…Hepcidin is a stress-inducible peptide of the biliary epithelia. In the bile, hepcidin help to protect against bacterial infections (Strnad et al, 2011). Studies in transgenic mice confirmed that C-reactive protein is protective against microbial pathogens thru its in vitro ability to bind microbes, activating the complement classical and alternative pathways as well as Fc RII (Szalai, 2002).…”
Section: Apr and Antimicrobial Activitiesmentioning
confidence: 99%